Finite and Infinite Arithmetic Progressions Related to Beta-Expansion - Bing Li; Chao Ma (Abstract and Applied Analysis)
Let 1<β<2 and ε(x,β) be the β-expansion of x∈[0,1). Denote by Aβ(x) the set of positions where the digit 1 appears in ε(x,β). We consider the sets of points x such that Aβ(x) contains arbitrarily long arithmetic progressions and includes infinite arithmetic progressions, respectively. Their sizes are investigated from the topological, metric, and dimensional viewpoints.